THE ROLE OF LITERACY ACTIVITIES ON INTELLECTUAL DEVELOPMENT OF CLASS 5 SDN BANJURMUKADAN THROUGH ANALYSIS OF DEVELOPMENT TASKS AND INVENTORY STUDENT DEVELOPMENT TASKS IN 2018 - Amanda Putri Nurjanah; Febriyanti Umi Khabibah; Muhamad Chamdani (Universitas Sebelas Maret, 2018)
Students need a pattern of learning literacy as a form of contribution to strengthening character values. This research aims to describe the role of literacy activities on the intellectual development of grade 5 students of Banjurmukadan Elementary School through Development Task Analysis (ATP) and Development Task Inventory (ITP). This research uses descriptive qualitative method, which consists of: data collection, data reduction, data presentation, conclusion drawing and verification, the results of the collected studies are then described and analyzed. The conclusion of this study is literacy activities have a good effect on students' intellectual development.